Clinic-pathologic features and gene fusion pattern of ALK and ROS1 in non-small cell lung cancer show association with household coal combustion - Chen, Ying; Huang, Yunchao; Ning, Huanqi; Chen, Xianmeng; Tan, Xiangxiu; Ding, Xiaojie (Translational Cancer Research; Vol 8, No 5 (September 30, 2019): Translational Cancer Research, 2019)
Background: Lung cancer induced by burning coal can be etiologically and clinically different from lung cancer caused by smoking. Despite previous work, the gene fusion patterns in lung cancer patients affected by household coal combustion still deserve further study. Methods: Non-small cell lung cancer (NSCLC) patients exposed to household coal use (HCU) were recruited from rural areas in China’s Yunnan Province, certain areas in this region had notably high lung cancer rate nationwide. Reverse transcription-polymerase chain reaction (RT-PCR) was used for detection of ALK, ROS1, RET and NTRK1 rearrangements. Eighteen studies on ALK fusions were summarized and compared with present work. Results: Among the 205 patients, there were 112 (54.6%) coal users and 96 (46.8%) smokers, union set had 145 (70.7%) subjects, in which 63 (30.7%) were double-positive for HCU and smoking. HCU patients featured with younger age and advanced stage. Union set patients covered larger age span (range, 40–82 years old), showed clear early-onset, and made the majority of stage IIIA–IV cases. Double-positive individuals were mainly in later stage, but with wider age span (range, 38–75 years old). In addition, 18 patients (8.8%) had EML4-ALK rearrangement, with apparently higher-than-average variant 3 ratio (77.8% vs. 44%). Five ROS1 fusion cases (2.5%) were identified, all were CD74-ROS1 (E6/E34), and had HCU experience. ALK and ROS1 fusions were mutually exclusive. Both ALK fusions and total gene rearrangement events (ALK and ROS1) showed association with HCU and overall exposure (tobacco and coal). Suggesting there could be unique gene fusion patterns in lung cancer patients affected by coal use. Conclusions: Present study found clinic-pathologic features and gene fusion patterns in NSCLC showed association with household coal combustion. Our findings may help evaluate the impact of coal use on the pathogenesis of lung cancer, and also highlight the significance of integrating different exposure histories into clinical and theoretical research.